Extrapulmonary Tuberculosis Cases: Five Years Experience - Bal, Isa Ahmet; Tartar, Ayse Sagmak; Akbulut, Ayhan; Demirdag, Kutbeddin (Galenos Yayincilik, 2021)
Introduction: Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis, which can affect any organ. The incidence of TB has increased due to the increase in the number of diseases and drugs that cause immunosuppression. The diagnosis of extrapulmonary TB (EPTB) is mostly clinical, histopathologic, radiologic, less frequent microbiological diagnosis. In our study, it was aimed to reveal the data helpful in the diagnosis by retrospectively examining the demographic and clinical data of the patients with EPTB. Materials and Methods: The patients who had a diagnosis of EPTB and were followed up between January 2012 and March 2017 in Firat University Hospital, Department of Infectious Diseases and Clinical Microbiology were included in the study. Data were analyzed using Statistical Packages for the Social Science 22 statistical program. Results: The study included 125 patients, 28.8% were male and 71.2% were female. The mean age was 46.3 +/- 17 years. Of the patients with EPTB diagnosed; 49% had lymphadenitis, 14% musculoskeletal system involvement, 3% miliary involvement, 10% genitourinary system involvement, 4% central nervous system involvement, 5% gastrointestinal system involvement, 5% mastitis, and 9% had other organ involvements. Patients most frequently presented with complaints of swelling, sweating and fever. Tuberculin skin test (TST) was positive in 61.1% of the patients and quantiferon test was positive in 71% of the patients. Growth in mycobacterial culture was found in 12.8% of our patients, polymerase chain reaction positivity in 6.4%, and acid-resistant staining positivity in 16.8%. Granuloma structures were seen in 81.9% of the patients who underwent histopathological examination, and caseification necrosis was detected in 64.7% of the granuloma structures. Conclusion: Tuberculosis must be considered in the differential diagnosis of infectious diseases in which no etiology is detected in areas where TB is common, such as our country. It is thought that none of the EPTB diagnostic methods have the sensitivity and specificity that can be used alone, and that the evaluation of TST or quantiferon can still be used for diagnosis. There is a need for new tests that have high sensitivity and specificity for the diagnosis of EPTB.
Ekstrapulmoner Tüberküloz Olgulari: Beş Yillik Deneyim
Keywords: Extrapulmonary tuberculosis; epidemiology; tuberculin skin test; quantiferon